Dampak Pengembangan Obyek Wisata Kayu Putih Terhadap Keuangan Dan Aktivitas Ekonomi Masyarakat Di Banjar Bayan - Suindari, Ni Made; Surya, Luh Putu Setyandarini (Universitas Pendidikan Ganesha, 2021)
Tourism is one sector that has an impact on the economy. The island of Bali, which is famous for its culture and natural beauty, has a variety of tourist attractions. One of the unique tourist attractions in Bali is the existence of a giant wooden tree that grows firmly in the Bayan Traditional Village area. The tree which the local community calls the eucalyptus tree is estimated to be hundreds of years old, growing behind a sacred place called Pura Babakan. The idea to develop this tree as a tourist attraction began in 2013 and began to be visited by tourists. Tourist arrivals certainly affect the economic activities of local residents. This study examines the economic impact of the community as a result of the development of eucalyptus tourism objects. Interviews and observations were conducted to collect primary data. The qualitative approach was carried out through structured interviews with informants. The condition of community settlements, the type of residential building is permanent with tiled floors and walls. The ownership status of the house is self-owned, built on land inherited by the family. All houses have electricity. Most people use gas stoves for cooking. Ownership of valuables such as cars, motorcycles, gold, refrigerators, televisions, cellphones, and computers, the acquisition is not related to the impact of tourism objects, but because of necessity. In general, the development of eucalyptus tourism objects has not had much effect on the economy of the Bayan Traditional Village community. This tourist attraction is only a giant tree with limited supporting facilities. In the future, there are still many potential villages that must be explored as a means of supporting and adding to the comfort of visitors.Â Â